Transformasi Kepemimpinan Kepala MA Salafiyah Bantarsari dalam Meningkatkan Mutu Pendidikan Era Digital : Analisis Habitus dan Arena ( Bourdieu ) - Fatikhatussyangadah Fatikhatussyangadah; Muh. Hanif (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This qualitative study aims to analyze the leadership transformation of the principal of MA Salafiyah Bantarsari in improving educational quality in the digital era through Pierre Bourdieu’s concepts of habitus and field. The study employed a case study approach, with data collected through in-depth interviews, observations, and documentation. The findings reveal that leadership transformation is carried out through strengthening organizational culture, utilizing educational technology, and developing teachers’ digital competencies. The principal’s leadership habitus is shaped by leadership experience, organizational culture, and perceptions of digital technology, which influence leadership strategies in responding to educational changes. Furthermore, the principal successfully utilizes various forms of capital, including cultural capital through mastery of educational technology, social capital through collaboration with external institutions, economic capital through the provision of digital facilities, and symbolic capital through community trust in the madrasa. Transformational leadership practices are implemented through the use of the E-Masba application, Learning Management Systems (LMS), digital learning media, technology training for teachers, and the strengthening of digital culture in both learning and educational administration. This study confirms that leadership transformation plays a significant role in enhancing educational service effectiveness, teachers’ digital competencies, and overall educational quality in the digital era.